Cenzura polityczna wobec karykatury. Doświadczenia francuskie II połowy XVIII i pierwszej połowy XIX wieku. Przyczynek do walki o wolność słowa - Sobczak, Jacek (Czasopismo Prawno-Historyczne, 2018)
Caricature is one of the forms of artistic expression and it has a similar role to satire. Consequently, some people consider caricature to be one of the forms of satire. Caricature has its origins in ancient times. The history of caricature is illustrated by political changes that civilization experienced. The administrative authorities attempted to fight caricature in numerous countries and France was one of them. This process is a part of the history of censorship that began in Roman times. Afterwards, it developed further during the Christian period of the Middle Ages until the 19th century. Unfortunately, this procedure is present in certain areas even today. The most interesting solutions were the ones adopted in France. Moreover, it is worth noting that the phenomenon of institutionalization of censorship was not the only characteristic element in France. There were also censorship bodies present in the country despite the formal constitutional declarations of freedom of speech.